2008
DOI: 10.1038/cmi.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIR Genotypes and Haplotypes with Susceptibility to Chronic Hepatitis B Virus Infection in Chinese Han Population

Abstract: Killer immunoglobulin-like receptor (KIR) genes can regulate the activation of NK and T cells upon interaction with HLA class I molecules. Hepatitis B virus (HBV) infection has been regarded as a multi-factorial disorder disease. Previous studies revealed that KIRs were involved in HCV and HIV infection or clearance. The aim of this study was to explore the possibility of the inheritance of KIR genotypes and haplotypes as a candidate for susceptibility to persistent HBV infection or HBV clearance. The sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…1,2 Some previous studies identified a relationship between KIR genotypes and outcomes of several infections, such as human immunodeficiency virus, 5,12 CMV, 13 hepatitis B virus, 14 and hepatitis C virus. 15,16 Our data demonstrate for the first time the role of KIRs in the pathogenesis of BKV infection.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Some previous studies identified a relationship between KIR genotypes and outcomes of several infections, such as human immunodeficiency virus, 5,12 CMV, 13 hepatitis B virus, 14 and hepatitis C virus. 15,16 Our data demonstrate for the first time the role of KIRs in the pathogenesis of BKV infection.…”
Section: Discussionmentioning
confidence: 98%
“…Genetic evidence suggests that KIR and MHC class I polymorphisms play a significant role in determining the course of infection for several human pathogens, including hepatitis C virus (8), hepatitis B virus (9, 10), human papilloma virus (11, 12), HSV (13), and HIV (14, 15). However, studies addressing the functional implications of these observations have been limited by the lack of a suitable animal model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that KIR2DL3:HLA-C1 homozygosity was protective in a Chinese population, 14 whereas KIR2DL1:HLA-C2 was associated with HBV infection susceptibility according to subsequent findings. 15,16 Unfortunately, studies of KIR/HLA-C interactions in Brazilian populations are focused on autoimmune diseases and infectious diseases other than hepatitis B.…”
mentioning
confidence: 99%